If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x=6x)
We move all terms to the left:
(5x-(6x))=0
We add all the numbers together, and all the variables
(-1x)=0
We get rid of parentheses
-x=0
x=0/-1
x=0
| 4(10+3)-(-2x+3)=6(4x+6)+18x-27 | | X÷3-3x-7÷5=x-2÷6 | | 1/2(6x+13)=3x+5 | | -8x-16-28=6x-20-2x | | 3(x2-2)+12=47 | | |x|=13.4 | | 4x/5=1 | | 548+29.5(u)=2,023 | | 8x-6=18x+4 | | v−–2–2=–3 | | 2(-0.8)-y=5 | | -4x=-6x+2(x-4) | | 4(4x+5)=5(3x-1) | | 5+6n=4 | | (10y)^3=0 | | 3(-0.8)+y=-9 | | 4(3x-6)=3(x-6.5) | | -4(-9-4x)=5(3x+8) | | 8x-4=14+6x | | 4x+26=7x+7 | | −x/3+10=18x= | | 3n-8n=-20 | | 2X+2-2y=0 | | -51=-3-6x | | −x3+10=18 | | 15(3n+8)n=13 | | 4y-12=-7+8y | | 3x-4+12=2x-8 | | −x3+10=18x= | | 2(3x-7)=-22 | | -4(7x+7)=168 | | -4(7x+7)=169 |